Mechanical ventilation in dogs and cats with tick paralysis - O'Keeffe, Tess; Donaldson, Rebekah E. (Frontiers in Veterinary Science, 2023)
Respiratory failure from tick paralysis (TP) is an important cause of mortality in cats and dogs in Australia, occurring from a combination of respiratory muscle paralysis, upper respiratory tract obstruction and pulmonary disease. Patients may require positive-pressure ventilation in management of any combination of hypoxemia, hypoventilation or respiratory fatigue, but may also require airway management due to laryngeal paralysis. No single ventilation strategy is recommended due to the heterogenous disease presentations. Lung protective ventilation should be used in patients with pulmonary disease. Due to local and systemic effects of TP, patients are at higher risk of complications such as aspiration pneumonia and corneal ulceration and may have additional intravenous fluid and nutritional considerations. Treatment with hyperimmune serum is associated with improved outcomes. Prognosis is considered good with documented survival to discharge (STD) of 52.6–77% for animals with TP ventilated with lung disease and 90.5% for animals without lung disease. Median reported duration of ventilation for TP ranges from 23 to 48 h (range 3 h−10 days). The severity of individual neuromuscular signs and the presence of associated conditions such as aspiration pneumonia and laryngeal paralysis may necessitate longer periods of mechanical ventilation. This review aims to summarize the current recommendations regarding indications, management and prognosis of cats and dogs undergoing MV for TP and to identify areas for future research.